Genomics of Type 1 Diabetes in Ukraine Initiative - K. Shchubelka; Walter W. Wolfsberger; O. Oleksyk; et. all (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Type 1 diabetes (T1D) is a complex autoimmune disorder with a strong genetic component. While genome-wide association studies have identified over 90 loci associated with T1D, the contribution of rare, coding, and population-specific variants remains poorly explored. A new international collaborative effort, based in Ukraine in partnership with Uzhhorod National University and coordinated with Oakland University, was launched to enrol 20,000 individuals (10,000 clinically confirmed T1D cases and 10,000 ethnically/geographically matched controls) from Ukraine and neighbouring Poland, generate high-coverage whole-exome sequences (WES) and genome-wide genotypes, and create an open, GDPR-compliant data resource. Genomics of Type 1 Diabetes in Ukraine initiative established a nationwide network of endocrinologists linked to a –80 °C biobank and REDCap phenotyping platform at Uzhhorod National University (Uzhhorod, Ukraine). Peripheral-blood DNA is extracted locally; WES (Illumina NovaSeq X, Twist capture) and array genotyping are performed at the Regeneron Genetics Center (NY, USA), with joint calling and quality control on the HPC cluster (Oakland University, MI, USA). Despite wartime logistical constraints, more than 12,000 volunteer participants were recruited across Ukraine, and high-quality exome and genotype data were generated for 10,000 samples for a case-control genome-wide association study. Association testing is underway to confirm the known and identify several new Eastern-European-specific coding variants; re-analysis of exomes also enabled molecular re-diagnosis of monogenic diabetes in multiple families. A de-identified web portal (genes.uzhnu.edu.ua) and mirror deposition in the European Nucleotide Archive provide tiered access to raw and summary data. Pilot long-read HLA sequencing, stool metagenomics, and whole-blood RNA-seq are underway to extend the resource and enable future collaborations. The project has demonstrated the feasibility of large-scale genomics in a resource-constrained setting impacted by the ongoing war and delivers the first substantial T1D variant catalogue from Eastern Europe and will scale to 20,000 participants and multi-omics integration, is poised to refine genetic risk prediction, illuminate novel disease pathways, and strengthen precision-medicine infrastructure in the region.